Novel peptidomimetics related to gonadotropin-releasing hormone (GnRH)1. Issue 9 (2nd September 2015) - Gelain, Arianna; Rizzi, Luca; Legnani, Laura; Pacini, Aurora; Spyridaki, Katerina; Karageorgos, Vlasios; Liapakis, George; Villa, Stefania
<x xml:space="preserve">Abstract</x> Novel GnRH I and II analogues were designed and synthesized by Solid Phase Peptides Synthesis (SPPS), since GnRH has antiproliferative properties, but poor metabolic stability.